PPL Student Mentoring to Improve Santri Learning Motivation at Fath Darut Tafsir Pesantren - Yuli Noprianti; Derysmono Derysmono; Isma Muhsonah; Fahmi Rusdi Toha; Muhammad Yusuf Siddik (Unity Academy, 2026)
Santri learning motivation in pesantren needs continuous strengthening because classroom dynamics, boarding-school routines, and different learning abilities often lead to passive participation, limited confidence in discussion, and inconsistent muroja’ah discipline. This community engagement activity aims to describe the role of Field Experience Practice (PPL) students in improving santri learning motivation and character formation at Pondok Pesantren Fath Darut Tafsir Bogor. The method used was a descriptive qualitative community engagement approach based on reflective experience through initial observation, needs mapping, learning planning, mentoring implementation, and reflective evaluation. Data were collected through direct observation, teaching practice, activity documentation, reflective notes, informal interaction with santri, and supervising-teacher feedback. The program was conducted for approximately six months through Fiqh Wadhih, general fiqh, arts and culture, Qur’an halaqah, muhadharah, and Nisa’iyah activities. The results show qualitative-linguistic changes: santri who initially tended to be passive became more willing to answer questions, ask questions, discuss, complete tasks, and follow muroja’ah more consistently. The contribution of this activity lies in strengthening PPL mentoring strategies based on contextual learning, direct practice, creative media, verbal reinforcement, and moral role modeling.